ASSESSMENT OF THE PRICE FACTOR IMPACT ON THE FOREIGN TRADE INCOME CHANGE (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2026)
Foreign trade in base metals is an important part of the development of the economy of Ukraine. The products of the metallurgical industry are in demand on the world market, and their export ensures the formation of a significant part of foreign trade revenues. The purpose of the article is a quantitative analysis of the impact of the price factor on changes in foreign trade revenues of the leading group of Ukrainian export goods – base metals. This goal is defined in the hypothesis that the price factor has a significant impact on the volume of trade revenues in foreign economic activity. The methodological basis of the study is the determination of price "terms of trade" based on price indices, as well as the use of the index method to assess the impact of the price factor on trade profit (loss). A number of trends in the development of Ukraine's foreign trade have been identified, in particular, the rapid growth of the negative balance in the main groups of commodity exports and the predominance of the growth rates of import prices compared to the growth rates of exports. Based on the calculations, it was established that in 2023 trade loss from trade in base metals amounted to 390.8 million USD, and in 2024 – 386.4 million USD, respectively. It is proved that the trade loss in the base metals group was largely due to the influence of the price factor in the ferrous metals group. In 2023, the trade loss in trade in ferrous metals amounted to 386.0 million USD, which is 98.7% of the total trade loss in the base metals group. In 2024, the trade loss in the commodity subgroup "ferrous metal products" amounted to 183.7 million USD, or 98.4% of the total trade loss. The calculation of trade losses made it possible to outline the scale of losses to the Ukrainian economy from the deterioration of the "terms of trade." The study made it possible to identify the prospects of the studied goods in foreign trade from the point of view of state regulation of the development of the national economy.
Keywords: foreign economic activity; export; import; trade profit; price factor; national economy